Effect of Cloud Accounting as income statement on Accountant Performance - Aini, Qurotul; Anoesyirwan, Anoesyirwan; Ana, Yuli (Pandawan, 2020)
A simple and secure security accounting system is a system needed by various large and small companies where of course the company is never separated from accounting in order to process financial expenditures and revenues owned by companies that have a purpose to make a profit. Efforts to achieve success in a company can be seen from financial management which can be monitored and can be managed properly so that finance can be controlled well too, for that accuracy is an important role so with the company's cloud accounting it can be easier to monitor and also manage financial well, so it will be easier to make income / loss statements. cloud accounting provides a user friendly look that can certainly facilitate users. The purpose of this study is so that companies can pay more attention to monitoring and managing finances well so that it can facilitate the making of income statement . In this study took place used observational research methods and field library studies so that the system made can meet the existing needs of the company.